Plane Stress Problem of Plastic Forming of Cylindrical Shells Made From Coated Metal Sheet - Sołkowski, T. (Engineering Transactions, 1991)
The method of characteristics is applied to salve the axially symmetric problem of plastic yielding of coated metal sheets under plane stress conditions, in spite of the layered structure of the shell. The material properties are modelled by introducing different Lankford anisotropy factors and different strain-hardening curves for individual layers. The relations derived for the characteristics are then applied to salve the problem of press forming of cylindrical shells on a fiat or conical die without a blankholder. The numerical examples illustrate the effect of zinc and tin coats on the forming stresses of coated steel sheets.